Work Effort in the UK: Trends and Explanations - J. Ignacio Gimenez-Nadal; Almudena Sevilla (Institute of Labor Economics (IZA), 2022)
This paper links detailed 24-hour diary surveys in the United Kingdom (UK) over the last four decades to provide evidence on the increase in work effort in three specific dimensions: timing, nature, and composition. We rule out possible explanations behind these trends, finding that the decrease in the frequency of on-the-job leisure is more pronounced for workers in routine task-intensive occupations. Alternative supply- and demand-side explanations, such as changes in the relative preference for leisure, or the increase in offshoring, or competition for jobs, cannot explain our results. Our findings posit the amount and the frequency of on-the-job leisure as a measure of work effort, and the routine-biased technological change experienced during this period lies at the root of the increase in work effort in the UK.
Keywords: D63; J22; J23; J24; J31; J62; 330; labor supply; time-use; work effort; routine-biased technological change